RNAi-Mediated Knockdown of Imaginal Disc Growth Factors (IDGFs) Genes Causes Developmental Malformation and Mortality in Melon Fly, Zeugodacus cucurbitae - Ahmad, Shakil; Jamil, Momana; Fahim, Muhammad; Zhang, Shujing; Ullah, Farman; Lyu, Baoqian; Luo, Yanping (Frontiers in Genetics, 2021)
This study reports the first successful use of oral feeding dsRNA technique for functional characterization of IDGFs genes (IDGF1, IDGF3_1, IDGF4_0, IDGF4_1, and IDGF6) in melon fly Zeugodacus cucurbitae. Phylogenetic and domain analysis indicates that these genes had high similarity with other Tephritidae fruit flies homolog and contain only one conserved domain among these five genes, which is glyco-18 domain (glyco-hydro-18 domain). Gene expression analysis at different developmental stages revealed that these genes were expressed at larval, pupal, and adult stages. To understand their role in different developmental stages, larvae were fed dsRNA-corresponding to each of the five IDGFs, in an artificial diet. RNAi-mediated knockdown of IDGF1 shows no phenotypic effects but caused mortality (10.4 %), while IDGF4_0 caused malformed pharate at the adult stage where insects failed to shed their old cuticle and remained attached with their body, highest mortality (49.2 %) was recorded compared to dsRNA-GFP or DEPC. Silencing of IDGF3_1 and IDGF4_1 cause lethal phenotype in larvae, (17.2 %) and (40 %) mortality was indexed in Z. cucurbitae. IDGF6 was mainly expressed in pupae and adult stages, and its silencing caused a malformation in adult wings. The developmental defects such as malformation in wings, larval-larval lethality, pupal-adult malformation, and small body size show that IDGFs are key developmental genes in the melon fly. Our results provide a baseline for the melon fly management and understanding of IDGFs specific functions in Z. cucurbitae.